Development of a Desmos-Assisted Flipbook E-Module to Improve Mathematical Problem-Solving Ability - Nunu Nurhayati; Erika Awaliah Nursyafitri; Nuranita Adiastuty (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The ability to solve problems in mathematics is an essential competency that every student must have because in fact, this ability is still low. Many students still find it difficult when they have to solve story-based problems, especially on the topic of geometric transformations. The limited teaching materials that support learning also become an obstacle, because the available media are not interactive or interesting enough to facilitate students' understanding of the material. Based on these problems, this research is focused on the development of a Project Based Learning (PjBL)-based flipbook e-module designed to improve mathematical problem-solving skills on geometric transformations. The type of research used is research and development (R&D) by applying the ADDIE model as a reference for product development. The research subjects were 26 students of grade IX A of SMP Negeri 1 Hantara. Data were collected using questionnaires, interviews, and tests. The assessment results from three material experts obtained a feasibility percentage of 87% while from two media experts 81% were categorized as very valid. The results of the practicality test using a questionnaire obtained a percentage of 97% from teachers and 95% from students (very practical). Effectiveness is shown through N-Gain of 0.71 with a high category because it is in the range of N-Gain> 0.70 from an average pre-test of 24.31 and post-test of 75.95. This e-module is proven to have a good level of validity, practicality, and effectiveness in helping improve students' mathematical problem-solving abilities. Further research is expected to be able to expand the scope of subjects and emphasize other indicators of mathematical problem-solving abilities in media development.